2009 International Conference on Sustainable Power Generation and Supply 2009
DOI: 10.1109/supergen.2009.5348088
|View full text |Cite
|
Sign up to set email alerts
|

Lightning protection of wind turbines — A comparison of lightning data & IEC 61400-24

Abstract: IEC 61400 -24 dealing with lightning protection of wind turbines was first introduced in 2002. This was initially developed as a technical report. Since then, wind power has been rapidly developing with wind turbine manufacturers developing larger wind turbines which are at an increased risk of lightning strikes. With the move of large wind farms offshore, maintenance of wind turbines also becomes harder owing to the harsh and unpredictable environment. Limiting lightning strike damage on wind turbines becomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
9
1
1
Order By: Relevance
“…which could be equally well applied for the negative upward-initiated lightning strokes. Equation (34) with equations (4), (15), (17) and (35) could be used to estimate the (long-term) average number of expected lightning strikes to WTs, of negative polarity upward and downward initiated lightning combined. This has been carried out for the previously treated example of rather extreme WT exposure (Section 5).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…which could be equally well applied for the negative upward-initiated lightning strokes. Equation (34) with equations (4), (15), (17) and (35) could be used to estimate the (long-term) average number of expected lightning strikes to WTs, of negative polarity upward and downward initiated lightning combined. This has been carried out for the previously treated example of rather extreme WT exposure (Section 5).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, because of the certain amount of upward-initiated lightning strikes, there is a clear tendency that the frequency distribution of lightning current amplitudes, associated with WT incidence, will be associated with lower median values, as has been observed on off-shore wind farms. 35,36 Additionally, median current of negative upward-initiated lightning to Gaisberg tower (100 m tall and located on a mountain 1287 m above the sea level) is estimated to be 9.2 kA. 37 Furthermore, it has been shown that median current amplitudes associated with upward-initiated lightning have very similar values to those of subsequent return stroke currents and rocket-triggered lightning currents.…”
Section: Comparison Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability distribution of lightning current values shows that the wind turbine blades capture lightning strikes with lower peak currents in comparison to the windvane [7]. More than 88% of lightning attachments occur within the outermost 1 m of the blade tip [8], but increased risk of inboard puncture for lightning strike of smaller current than 20 kA is also noticed [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to radars, all the protection methods and restrictions have to be considered at all levels, starting with the design, in order to avoid additional expenditure and manhours being necessary for improvements once in use. During intensive studies and research over the past decades, scientists have been looking at the effect of lightning on wind turbines [98], [99], [104], [105] by compiling statistics about damage events or creating several databases with over 4000 turbines. Table 5-1 gives an overview of data relating to the frequency of lightning damage collected in these databases.…”
Section: Wind Turbinesmentioning
confidence: 99%